2018
DOI: 10.1590/1981-22562018021.180076
|View full text |Cite
|
Sign up to set email alerts
|

Leprosy in the elderly population of Alagoas

Abstract: Objective: to describe the epidemiological profile of elderly persons with leprosy in the state of Alagoas. Method: a descriptive epidemiological study of leprosy cases among the elderly reported to the Disease Notification Information System between 2005 and 2015 was carried out. Results: a total of 896 cases were identified, with a predominance of 60-69 years old (60.5%), who were male (50.4%), had no schooling (34.8%), no source of income (54.1%), multibacillary forms of the disease (67.9%), and a high pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
2
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 14 publications
2
5
2
8
Order By: Relevance
“…On the other hand, some studies have shown that men neglect their health 28 , 29 . According to the MF and some studies carried out in Bahia, Pará, and Alagoas, there is a higher incidence of leprosy in men, which differs from what has been observed in our study, suggesting the existence of a higher number of hidden, chronic and transmission cases in the male population of Arapiraca 11 , 30 , 31 , 32 .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…On the other hand, some studies have shown that men neglect their health 28 , 29 . According to the MF and some studies carried out in Bahia, Pará, and Alagoas, there is a higher incidence of leprosy in men, which differs from what has been observed in our study, suggesting the existence of a higher number of hidden, chronic and transmission cases in the male population of Arapiraca 11 , 30 , 31 , 32 .…”
Section: Discussioncontrasting
confidence: 99%
“…The diagnostic delay is reinforced by the increase in new MB cases, from 26.08% in 2008 to 52.94% in 2017. Despite the higher prevalence of the dimorphic form recorded in other studies, the tuberculoid form predominance (38.7%) found in our study may be a worrisome result since it is an indication that the disease affects individuals with a more resistant immunological profile, which was also observed in Juazeiro, Bahia 23 , 31 , 40 .…”
Section: Discussioncontrasting
confidence: 79%
“…Para análise dos dados, os estudos incluídos foram classificados em três categorias temáticas: "Aspecto físico: comprometimento da capacidade funcional e dependência do idoso", "Aspecto psicológico: principais afecções, estigma e preconceito" e "Aspecto social: relações sociais, autonomia e qualidade de vida do idoso". (CHENG et al, 2012;SILVA et al, 2014;NOGUEIRA et al, 2017;SOUZA et al, 2017a;DINIZ;MACIEL, 2018;SILVA et al, 2018).…”
Section: Resultsunclassified
“…Destacam-se as altas proporções de pessoas de cor da pele negra e sem instrução ou com ensino fundamental incompleto, entre os casos de hanseníase, em todas as faixas etárias, com 64,8% e 66,1% entre os idosos, respectivamente. Tais achados foram semelhantes àqueles de Silva et al 13 e Diniz & Maciel 8 . Outros estudos revelaram associação entre altas taxas de detecção de hanseníase e fatores socioeconômicos precários, como baixa escolaridade e alto índice de vulnerabilidade social 14,15 .…”
Section: Discussionunclassified